Assessment of Water Demand From Urban and Rural Area in Kota Bharu, Kelantan - Fauzi, Siti Nur Farzilah; Ts. Dr. Sabariah binti Musa, (Recent Trends in Civil Engineering and Built Environment, 2021)
Surface water is any body of water that is located on top of Earth’s surface including rivers and lakes. It is more easily accessible than groundwater and becomes an important source for domestic purposes especially for residents that live in rural areas. One of the most widely used types of surface water is a river. This study was conducted at Pengkalan Chepa River, which is located at Kelantan. The pollution of this river is because the surrounding area is an urban development, accommodating crowded and industrial activities. Therefore, the objective of this study is to evaluate the factor of minimal usage of river water among the residents in Kelantan. The study was conducted with a quantitative method that used questionnaire form instrument. A total of 50 respondents provide feedbacks on the questionnaire. Data obtained from the questionnaire were analyses using Statistical Packages for Social Science (SPSS). The results from the survey show that 80% of respondents from all districts in Kelantan does not consume river water. Pengkalan Chepa River is located at district of Kota Bharu and from the online survey by google form discussed that Kota Bharu is the top one that does not use river water due to the use of other water sources such as groundwater and private water meters. The implication of work towards this quality of surface water can contribute to environmental engineer in doing a future project regarding in improving the river water and gradually meet the standard of better water.